GDNF secreted by nerves enhances PD-L1 expression via JAK2-STAT1 signaling activation in HNSCC. (2nd November 2017) - Lin, Chengzhong; Cao, Wei; Ren, Zhenhu; Tang, Yu; Zhang, Chunye; Yang, Rong; Chen, Yiming; Liu, Zheqi; Peng, Canbang; Wang, Lizhen; Wang, Xu; Ji, Tong
ABSTRACT: Programmed death ligand 1 (PD-L1) functions as a key immune inhibitory factor by binding with its receptor, programmed death 1 (PD-1), to induce immune cell dysfunction and escape of the immune system. However, the mechanisms of PD-L1 expression under growth factor stimulation are not well characterized. Here, we demonstrate a novel role for glial cell line-derived neurotrophic factor (GDNF) in upregulating PD-L1 expression in head and neck squamous cell carcinoma (HNSCC). The expression and correlation of PD-L1, GDNF and perineural invasion (PNI) status were evaluated by bioinformatics analysis of TCGA database and IHC assays from 145 HNSCC patients. PD-L1 expression was investigated by flow cytometry, Western blot and real-time PCR analyses in HNSCC cells after GNDF incubation. The cell signaling pathways activated by GDNF were analyzed with an antibody array and blocked by specific signaling inhibitors in cancer cell lines. PD-L1 expression was significantly higher in cancer cells that exhibited PNI in the HNSCC specimens, and elevated PD-L1 expression was significantly correlated with GDNF levels. GDNF not only enhanced cancer cell PNI in a co-culture of dorsal root ganglions and cancer cells but also had a potent role in inducing PD-L1 expression through the JAK2-STAT1 signaling pathway. Moreover, a JAK2 inhibitor attenuated GDNF-induced PD-L1 and enhanced tumor cell susceptibility to NK cell killing. Our findings provide clinically novel evidence that nerve-derived GDNF can increase PD-L1 levels in cancer cells around the perineural niche and that regulatory signaling is critical for cancer cell escape from immune surveillance in the nerve-cancer microenvironment.